Strategi Guru dalam Mengembangkan Nilai Agama dan Moral pada Anak Usia 4-6 Tahun - Rahmatullah, Ari Abdul Kohar; Ruswandi, Agus; Azizah, Annisa Nur; Nurkholipah, Nurkholipah; Putriani, Puput (Jurnal Keislaman, 2024)
This research is motivated by the frequent occurrence of children committing acts such as bullying, violence, and a lack of politeness and courtesy. Among the factors causing this is that the teacher's strategy in teaching religion and morals is not in accordance with the learning objectives. This study aims to determine the teacher's strategy for teaching religious and moral values to children aged 4-6 years. The research approach used a qualitative approach through the case study method. The data source for this research is Early Childhood Education (ECE) teachers at Kober Raudhotul Jannah Cicalengka and RA Arraudotunnur Garut Regency, with as many as five informants. Data analysis techniques have three main steps: data reduction, data display, and verification. The results concluded that teachers do not fully understand the learning objectives of religion and morals at the PAUD level. Teachers use a variety of methods in accordance with predetermined learning objectives. The methods used by teachers include habituation methods, exemplary singing, role-playing, and tourism work